Post‐transplant complications, patient, and graft survival in pediatric and adolescent kidney transplant recipients at a tropical tertiary care center across two immunosuppression eras. (19th January 2021) - Mohapatra, Anjali; Valson, Anna T.; Annapandian, Vellaichamy M.; David, Vinoi George; Alexander, Suceena; Jacob, Shibu; Kakde, Shailesh; Kumar, Santosh; Devasia, Antony; Vijayakumar, Theophilus S.; Tamilarasi, Veerasamy; Jacob, Chakko Korula; et al.
Abstract: Background: We report pediatric PAKT patient and graft outcomes at a large tropical tertiary center spanning two transplant eras. Methods: In this retrospective cohort study, all children ≤18 years who underwent kidney transplantation at our center between 1991 and 2016 were included. Data pertaining to their baseline characteristics, post‐transplant events, and outcome were retrieved from transplant records and compared between transplant eras (1991‐2005 and 2006‐2016). Results: A total of 139 children (mean age 15.2 ± 2.9 years) underwent PAKT during this period. The incidence of UTIs, CMV disease, BKVN, invasive fungal infections, new‐onset diabetes after transplant, leucopenia, and recurrent NKD was higher in the 2006‐2016 era ( P  < .001 for all), while 1‐year cumulative BPAR was comparable ( P  = .100). Five‐year graft and patient survival in the two eras were 89.9% and 94.2% ( P  = .365) and 92.1% and 95.3% ( P  = .739), respectively. Incidence of CMV disease, BKVN, graft loss, and death was lower in the calcineurin withdrawal group. Non‐adherence accounted for 36% of graft loss; infections caused 43.7% of deaths. On multivariate Cox proportional hazards analysis, independent predictors for graft loss were UTIs and blood transfusion naïve status and for death were serious infections and glomerular NKD. Conclusions: PAKT in India has excellent long‐term graft outcomes, though patient outcomes remain suboptimal owing to a high burden of infections. Current immunosuppression protocols need to be re‐examined to balance infection risk, graft, and patient survival.